SISTEM REKRUTMEN DAN KADERISASI PDI PERJUANGAN KABUPATEN KENDAL ERA REFORMASI (Studi Kasus Oligarki di Kabupaten Kendal) - Rizki Khoiruly; Susilo Utomo; Rina Martini (Journal of Politic and Government Studies, 2013)
Political party is one of democracy consolidation agent which replaces personal-authority based feodalistic system into people-authority based democracy system. Considering the success of democracy consolidation by political party can be measured from good recruitment system and cadre system, clear political party’s orientation, and political configuration which is based on principle and method of democracy. This analytical writing starts from the idea of PDI Perjuangan as a big political party in Indonesia which has militant supporter base since this party takes “Soekarnoisme Ideology”. PDI Perjuangan is identical with a leadership of Soekarno’s offspring by the emergence of Megawati and Puan Maharani within party’s leadership. PDI Perjuangan Kendal county is identical as well by the emergence of Hendy Boedoro’s family. Twice of governmental election in Kendal county that was held directly won by PDI Perjuangan. The purpose which is going to approach in this reaserch is to know recruitment pattern cadre process, and political institution which is run by PDI Perjuangan Kendal county. Reaserch result shows that it is a tendency into oligarchy culture in PDI Perjuangan Kendal county. This is caused by domination of party leadership by the family of Hendy Boedoro. Party’s dependence toward in-charge party’s elite to strengthen cultural oligarchy. Such thing can be inffered in party’s leader election and candidate election of regent which was held by PDI Perjuangan Kendal county dependent on figures Hendy Boedoro and Widya Kandi Susanti. PDI Perjuangan has centralistic tendency with full authority which is owned by central PDI Perjuangan for policy in county level such as having the right of declaring the chairman who will be advised by PDI Perjuangan.Keywords: recruitment system, cadre system, oligarchy culture